Analisis Sosiologi Sastra Terhadap Perkembangan Tokoh Lail Dalam Novel Hujan Karya Tere Liye - Raka Febiansyah Putra; David Setiadi; Fauziah Suparman (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2026)
Character development in a novel can basically occur due to environmental factors or social dynamics experienced by the character. The main objective of this study is to explain the development of characters who are affected by their environment and social factors. This research was conducted using qualitative methods, which describe the character development of Lail in the novel Hujan by Tere Liye. The results of this study explain the intrinsic elements of Tere Liye's novel Hujan in the form of plot, characterization, and setting. It also explains three clarifications of literary sociology, namely the social function of the author, literature as a reflection of the times, and the social function of literature. The character development that occurs in a literary work is influenced by the dynamics experienced by the characters. Other roles, such as supporting characters, also contribute to this development. The author also plays a role as the developer of the story.